Secondary metabolite research in Malaysia: current status and future prospects - Hashim, Yumi Zuhanis Has-Yun; Mohd. Salleh, Hamzah; Mohamad Puad, Noor Illi; Ahmad Fuad, Fazia Adyani; Eissa, Manar; Zainurin, Nur Aimi Aliah (IntechOpen, 2018)
Herbal medicine is gaining acceptance worldwide for their effective pharmacological effects and relative safety. Plants have metabolic pathways that lead to the production and accumulation of secondary metabolites such as alkaloids, glycosides, and terpenoids that exhibit various biological activities. Plant secondary metabolites have been the major foci of investigation for several years and have been successfully used against a number of communicable and noncommunicable diseases such as diabetes, cancer, and viral infections. This chapter will explore Malaysian plants, their secondary metabolites, and their biological/medicinal properties with a particular focus on some selected species under a national project. Other aspects such as plant tissue culture to produce secondary metabolites and a case study on the use of secondary metabolites in the prevention and treatment of dengue fever are also described. While a lot of effort has been put in, further research and development into plant secondary metabolites are needed including using the plant tissue culture approach toward reaching high-value herbal industry.